Complications and outcomes of cats with coxofemoral luxation treated with hip toggle stabilization using ultrahigh–molecular‐weight‐polyethylene or nylon (2009‐2018): 48 cats. Issue 5 (13th March 2021) - Espinel Rupérez, Jorge; Arthurs, Gareth I.; Hewit, Andrew; Langley‐Hobbs, Sorrel; Trostel, C. Todd; Phillips, Andrew S. J.; Keeley, Ben; Maritato, Karl C.; Jones, Stephen C.; Franklin, Phil H.; Whitelock, Richard; Fernández Pérez, Cristina; et al.
Abstract: Objective: To report overall rate and type of complications and outcomes of cats with coxofemoral luxation managed with hip toggle stabilization (HTS), to compare rate of postoperative complications and outcomes of cats treated with ultrahigh–molecular‐weight‐polyethylene (UHMWPE) or nylon, and to identify risk factors for reluxation and non‐excellent outcomes. Study design: Multi‐institutional retrospective cohort study. Sample population: Forty‐eight client‐owned cats. Methods: Medical records of cats that underwent HTS from 2008‐2018 using UHMWPE or nylon were reviewed. Univariable and multivariable logistic regression was performed to assess for factors associated with reluxation and non‐excellent outcome. Final outcome was obtained from owner questionnaire. Results: Intraoperative and postoperative complications were recorded in two (4.2%) and 11 (24.4%) cats, respectively. The most common postoperative complication was reluxation (n = 5 [11.1%]). Outcome was classified as excellent in 81.1% and good in 16.2% of cats after a median of 445.5 days (range, 53‐3720). No difference in rate of complications or outcomes was identified between UHMWPE and nylon. Performance of additional orthopedic procedures, occurrence of intraoperative complications, and non‐performance of capsulorrhaphy were associated with reluxation. Performance of additional non‐hip procedures (orthopedic/nonorthopedic) was associated with non‐excellent outcome. Conclusion: Hip toggle stabilization was associated with a low rate of intraoperative complications and reluxation and excellent long‐term outcomes in most cats. No difference in rate of postoperative complications or outcomes of cats treated using UHMWPE or nylon was identified. Cats that underwent additional orthopedic procedures had greater risk of reluxation. Clinical significance: Hip toggle stabilization is an effective technique for management of coxofemoral luxation in cats. Comparable results are expected using UHMWPE or nylon.